Penilaian Kinerja dengan Menerapkan Konsep Balance Scorecard di Mts Islamiyah Palangka Raya - Asmawati, Asmawati; Anwar Arifin; Iim Wasliman; Eva Dianawati; Arman Paramansyah (LPPM Institut Nasional Laa Roiba Bogor, 2023)
In general, many organizations still use performance measurement that puts more emphasis on the financial aspect, which is more commonly referred to as traditional performance measurement. Personal performance is measured only in terms of finances. Other performance such as increased competence and commitment of personnel, increased productivity, and business processes used to serve customers were ignored by management because measurement is difficult. The assessment of the financial aspect is measured based on the budget that has been made. The assessment is carried out by analyzing the variance (difference or difference) between actual and budgeted performance. The use of analysis of variance alone is not enough to measure performance, because the analysis of variance still contains variance limitations. The Balanced Scorecard is a measurement method with the best solution for managing business performance, because the Balanced Scorecard has the specialty of a comprehensive measurement scope, namely that in addition to considering financial performance it also considers non-financial performance. This study aims to find out how performance appraisal at MTS Islamiyah Palangka Raya uses the Balanced Scorecard method. The research used is qualitative with a descriptive qualitative approach and analyzed through observation, interviews and documentation. The results of this study describe that financial performance is considered good, as can be seen in the price indicators received from the School Operational Assistance (BOS) funds, and investment funds/committee contributions (SPP). From the customer perspective, the indicators used, namely the Number of New Customers, Number of Complaints, are said to be good. In the perspective of internal business processes found in the Balanced Scorecard it is said to be good, because the MTS Islamiyah Palangka Raya has carried out curriculum standards and teaching and learning process standards well. As for the growth and learning perspective, it shows that the performance of the MTS Islamiyah Palangka Raya has been good, this is shown by the amount of education and training carried out by the school. Keywords: performance, balanced scorecard, school.